Quality in rheumatoid arthritis care. Issue 4 (August 2015) - Mahmood, Sehrash; Lesuis, Nienke; van Tuyl, Lilian H.D.; van Riel, Piet; Landewé, Robert
Abstract: While most rheumatology practices are characterized by strong commitment to quality of care and continuous improvement to limit disability and optimize quality of life for patients and their families, the actual step toward improvement is often difficult. This is because there are still barriers to be addressed and facilitators to be captured before a satisfying and cost-effective practice management is installed. Therefore, this review aims to assist practicing rheumatologists with quality improvement of their daily practice, focusing on care for rheumatoid arthritis (RA) patients. First we define quality of care as "the degree to which health services for individuals and populations increase the likelihood of desired health outcomes and are consistent with current professional knowledge". Often quality is determined by the interplay between structure, processes, and outcomes of care, which is also reflected in the corresponding indicators to measure quality of care. Next, a brief overview is given of the current treatment strategies used in RA, focusing on the tight control strategy, since this strategy forms the basis of international treatment guidelines. Adherence to tight control strategies leads, also in daily practice, to better outcomes in patients with regard to disease control, functional status, and work productivity. Despite evidence in favor of tight control strategies, adherence in daily practice is often challenging. Therefore, the next part of the review focuses on possible barriers and facilitators of adherence, and potential interventions to improve quality of care. Many different barriers and facilitators are known and targeting these can be effective in changing care, but these effects are rather small to moderate. With regard to RA, few studies have tried to improve care, such as a study aiming to increase the number of disease activity measures done by a combination of education and feedback. Two out of the three studies showed markedly positive effects of their interventions, suggesting that change is possible. Finally, a simple step-by-step plan is described, which could be used by rheumatologists in daily practice wanting to improve their RA patient care.